Alcohol Abuse Among Minors in Tirtomoyo: Patterns, Contributing Factors, And Prevention Strategies - Firmansyah, Aditya Citra; Ayu, Hanuring (Jurnal Ilmu Hukum Kyadiren, 2025)
The abuse of alcoholic beverages by minors in Tirtomoyo District has been associated with an increase in various criminal acts, particularly physical abuse and sexual harassment. This study aims to identify the criminogenic factors contributing to this phenomenon, analyze the types of crimes that emerge as a result, and evaluate the effectiveness of prevention strategies implemented by both authorities and local communities. A qualitative-descriptive method was employed, utilizing interviews, direct observations, and documentation of police records from the Tirtomoyo Police Department spanning 2019 to 2022. The findings indicate that psychological instability, dysfunctional family environments, and a permissive social culture are among the primary contributing factors. Prevention efforts are currently conducted through community-based strategies encompassing repressive, preventive, and preemptive measures. The study concludes that effective mitigation requires cross-sector collaboration and the adoption of a context-sensitive legal framework to prevent the escalation of alcohol-related offenses among minors.